Hubungan Paparan Pestisida Dengan Gangguan Neuropsikiatri Pada Petani Hortikultura di Kecamatan Bukit Raya Pekanbaru - Faradini Faradini; Rahman Karnila; Suyanto Suyanto (SEHATI: Jurnal Kesehatan, 2023)
Indonesian agricultural sector always using of pesticides especially in horticultural farmers in Bukit Raya Pekanbaru district. However, the use of pesticides has a negative impact on the environment and health. One of the impacts on health is neuropsychiatric disorders such as cognitive disorders, anxiety and depression. This study was an analytic observational study, using a cohort approach. The research sample used a consecutive sampling technique with inclusion and exclusion criteria. The sample size is 32 people. The data analysis used the SPSS. There were significant differences in CHE levels (p=0.006), Moca-Ina scores (p=0.000), HAM-A (p=0.000) and HAM-D (p=0.000) during 3 months of exposure to pesticides. There is no significant relationship between the first CHE level and the first value of Moca-Ina (p=0.781), HAM-A (p=0.881) and HAM-D (p=0.605) and there is no significant relationship between the second CHE level and the second MocaIna (p=0.562), HAM-A (p=0.422) and HAM-D (p=0.869). The results of the multivariate analysis of smoking history score (p=0.021), working period (p=0.009), and spraying duration (p=0.006) are related to the MocaIna score on the delayed recall point. These three variables are able to explain the results of the delayed recall of 39.7 %.